2019
DOI: 10.1177/0961203319878493
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death 1 gene polymorphism as a possible risk for systemic lupus erythematosus in Egyptian females

Abstract: Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease with a suggested genetic basis. The newly identified human programmed cell death 1 gene could be associated with SLE susceptibility. We aimed to investigate the association between programmed cell death 1 polymorphism (PD1.3G/A (rs11568821) and PD1.5C/T (rs2227981)) with the risk of SLE in the Egyptian female population. This retrospective case–control study included 150 Egyptian females; 70 patients diagnosed to have SLE and 80 age-matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…This lack of the mutant TT genotype made it inconsistent with the HWE with the inability to detect the best model of inheritance of that SNP. A finding that was reported before on the same population by Abo El-khair et al [27] Several deviated SNPs have been detected to be out of the equation, however, they should not be excluded from the research, but additional analysis is needed on larger cohort. [28] The antitumor CD8+ T cells exhibit preferential expression of PD-1 protein leading to their exhaustion and functional impairment, which in turns lead to attenuated tumor-specific immunity with disseminating tumor progression.…”
Section: Resultsmentioning
confidence: 59%
“…This lack of the mutant TT genotype made it inconsistent with the HWE with the inability to detect the best model of inheritance of that SNP. A finding that was reported before on the same population by Abo El-khair et al [27] Several deviated SNPs have been detected to be out of the equation, however, they should not be excluded from the research, but additional analysis is needed on larger cohort. [28] The antitumor CD8+ T cells exhibit preferential expression of PD-1 protein leading to their exhaustion and functional impairment, which in turns lead to attenuated tumor-specific immunity with disseminating tumor progression.…”
Section: Resultsmentioning
confidence: 59%
“…3 Among Egyptian patients, different genetic polymorphisms have been studied and found to be associated with SLE as polymorphisms in the gene coding for the autoimmune regulator (AIRE), type I interferon (IFN) pathway, interleukin 27, programmed cell death 1 (PD1), tumor necrosis factor (TNF-α) and IFN-γ. [4][5][6][7][8] However, the role of the human leukocyte antigen-G (HLA-G) gene has not been addressed before among Egyptian patients.…”
Section: Introductionmentioning
confidence: 99%
“…PDCD-1.3 (rs11568821) gene polymorphism has been considered to be related to an overall cancer risk [24,27] and SLE [28]. Researchers have found a decreased overall cancer risk in case of PDCD-1.3, variant TC [24,27].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found a decreased overall cancer risk in case of PDCD-1.3, variant TC [24,27]. PD1.3GG genotype and G allele have been significantly more frequent in SLE patients [28]. Prokunina et al have found that this genetic variant would affect PD-1 mRNA level by changing the binding affinity of RUNX (a transcriptional factor of PD-1) [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation